Interplay between Y-box-binding protein 1 (YB-1) and poly(A) binding protein (PABP) in specific regulation of YB-1 mRNA translation - Lyabin, Dmitry N (Landes Bioscience, 2011)
YB-1 is a DNA- and RNA-binding protein that regulates expression of many important genes. Its deficiency or excess may pose threats, including malignant cellular transformation and metastasis, which explains the necessity of strict control over its amount at every level. As we showed previously, the 3′ untranslated region (UTR) of YB-1 mRNA contains a regulatory element specifically binding to YB-1 and PABP (PABPC1). Also, we showed that YB-1 selectively inhibits YB-1 mRNA translation, while PABP stimulates it in a poly(A) tail-independent manner. It was suggested that regulation of YB-1 mRNA translation involves competition between PABP and YB-1 for binding to the regulatory element. Here we offer cogent evidence for this model and add novel details to the mechanism of regulation of YB-1 synthesis. In experiments on regulatory element deletion we showed that it is this element that is responsible for a specific effect of YB-1 and PABP on YB-1 mRNA translation. Mutations eliminating only specific YB-1 affinity for this element suppressed the inhibitory effect of YB-1 and concurrently dramatically decreased the PABP stimulating effect. Mutations reducing only specific PABP affinity for this element, as well as spatial separation of the YB-1- and PABP binding sites, did not affect the YB-1 inhibitory action but completely abolished the positive PABP effect. Together, these results unambiguously prove direct inhibitory action of YB-1 on its mRNA translation, while the positive effect of PABP is realized through displacing YB-1 from the regulatory element.